Accurate and rapid prenatal diagnosis of the most frequent East Mediterranean β‐thalassemia mutations - Naja, R.P. (2004)
β‐Thalassemia is the most common genetic disorder in the Lebanese population. Of the 200 different mutations in the β‐globin gene that leads to thalassemia, the IVSI‐110 (29.87%), IVSI‐6 (20.74%), IVSI‐1 (14.07%), IVSII‐1 (9.13%), Cd29 (9.13%), and Cd30 (3.95%) mutations are the most frequent among Lebanese thalassemic patients. These mutations are also present at high frequencies in the East Mediterranean region. Due to this high prevalence of certain β‐thalassemia mutations, a rapid technique for the prenatal diagnosis of these mutations was implemented. The technique used is based on Real‐Time PCR quantification and melting curve analysis of the amplified fragment using the LightCycler. The DNA samples used for amplification were obtained from CVS or amniotic fluid. Six mutations were easily and efficiently detected using only 3 sets of probes. With this method, mutant genotypes can be easily distinguished from normal alleles. In prenatal diagnosis, the accuracy and the speed of testing are paramount. The method of prenatal β‐thalassemia mutations detection described here is efficient and fast, with the entire procedure including DNA preparation taking less than half a workday. It is safe, does not involve radioactivity, and is accurate showing 100% concordance with conventional DNA sequencing methods